2012
DOI: 10.4103/0019-557x.106421
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nutritional status by composite index for anthropometric failure: A study among slum children in Bankura, West Bengal

Abstract: A community-based cross-sectional study was conducted to find out the prevalence of composite index of anthropometric failure (CIAF) among 117 slum dwelling under-five children in Bankura town, West Bengal and its relation with some common socio-economic factors. Among study population, the prevalence of underweight was 41.6%, whereas CIAF was 80.3%. CIAF gave a near complete estimation of undernutrition unlike underweight. Children who were unimmunized, with more number of siblings, living in a nuclear family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 1 publication
4
30
4
Order By: Relevance
“…et al showed higher rates of composite index of anthropometric failure than compared to the present study. 6,[10][11][12][13][16][17][18]20,[23][24] Further, some studies found similar rates compared to our study. Studies by Bejarano IF et al done in Argentina had very low rates of composite index of anthropometric failure when compared to the present study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…et al showed higher rates of composite index of anthropometric failure than compared to the present study. 6,[10][11][12][13][16][17][18]20,[23][24] Further, some studies found similar rates compared to our study. Studies by Bejarano IF et al done in Argentina had very low rates of composite index of anthropometric failure when compared to the present study.…”
Section: Discussionsupporting
confidence: 82%
“…8 Many studies have used this concept in adding up the knowledge of composite index of anthropometric failure in their geographical locations. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] This study will add to the pool of such studies with an objective to study the rates of composite index of anthropometric failure in the children attending the Immunoprophylaxis clinic in a tertiary care hospital of Nagpur and to find associations with the socio demographic variables.…”
Section: Introductionmentioning
confidence: 99%
“…A study by GC mandal et al, showed 71.7% CIAF which is higher compared to current study while prevalence of Underweight was found to be 60.9% [13]. A cross sectional study conducted in Bankura, West Bengal, S Shit et al, showed 78.1% CIAF among Toddlers higher compared to current study while Underweight were only 38.5% which is lesser compared to that of current study [14]. Even in study by S das et al, Underweight (41.25%) was found to be lesser than CIAF (48.3%) and the margin was found to be lesser compared to other studies and the current one as well [15].…”
Section: Discussioncontrasting
confidence: 49%
“…1,17,18 In the current study, children who were from less educated mother and with more number of siblings were more likely to have anthropometric failure, Shit et al, Purohit et al, Maharashtra also observed similar findings regarding education level of mother and number of siblings in the family. 19,20 In the present study, malnutrition was more among females than males, among Muslims than Hindus, among children of low socioeconomic status groups, among children of less educated mothers and among those children who were not exclusively breastfed. The study strongly points toward the importance of proper infant feeding practices, proper nutrition, maternal education, and improved living conditions for reducing malnutrition among under-five children.…”
Section: Discussionmentioning
confidence: 40%